PHP programming with PEAR : XML, data, dates, web services, and web APIs : maximize your PHP development productivity by mastering the PEAR packages for accessing and displaying data, handling dates, working with XML and web services, and accessing web APIs /: XML, data, dates, web services, and web APIs : maximize your PHP development productivity by mastering the PEAR packages for accessing and displaying data, handling dates, working with XML and web services, and accessing web APIs. (©2006) - Unknown
No abstract available